Efektivitas E-modul Fisika Menggunakan Model Research Based Learning untuk Meningkatkan Kompetensi Perserta Didik SMA Kelas X di Era Revolusi 4.0 - Mutia Faizah Apriani; Yulkifli Yulkifli (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
Government regulations that require online learning during the Covid-19 pandemic are the driving force for the application of technology in learning in accordance with the demands of the 4.0 revolution era. In order for learning to run well, appropriate teaching materials are needed. One of the teaching materials that can be used is the physics E-module using the Research Based Learning model. This study aims to analyze the effectiveness of the application of e-modules to improve student competence in the 4.0 revolution era. The competencies analyzed are attitudes, knowledge and skills competencies. The skills needed in the 4.0 revolution era are called 4C skills, namely critical, creative, collaborative, and communicative thinking skills. The research method used is the quasi-experimental method. Based on the results of the study, it was concluded that the physics e-module with the Research-Based Learning model was considered effective for increasing the competence of attitudes, knowledge and skills of class X high school students in the 4.0 revolution era with a high category.